2017
DOI: 10.1016/j.anireprosci.2017.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Pentoxifylline effects on capacitation and fertility of stallion epididymal sperm

Abstract: The aims of this study were to determinate whether pentoxifylline (PTX) increases the motion parameters of fresh and frozen-thawed equine epididymal spermatozoa, to evaluate the tyrosine phosphorylation of frozen-thawed epididymal sperm in the presence of PTX and to determine whether the PTX-treatment of stallion epididymal sperm prior to freezing improves the fertility response of mares to a reduced number of spermatozoa per insemination dose. Fifty epididymis were flushed with a skim milk based extender with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…Moreover, this effect can be offset by the addition of pentoxifylline. Pentoxifylline, a phosphodiesterase inhibitor, increases cAMP concentration [ 46 , 47 ] and tyrosine phosphorylation [ 48 , 49 ]. In addition, the oral administration of essential phospholipids prevented a decrease in speed and an increase in the frequency of beating of the tail of the sperm.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, this effect can be offset by the addition of pentoxifylline. Pentoxifylline, a phosphodiesterase inhibitor, increases cAMP concentration [ 46 , 47 ] and tyrosine phosphorylation [ 48 , 49 ]. In addition, the oral administration of essential phospholipids prevented a decrease in speed and an increase in the frequency of beating of the tail of the sperm.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the addition of PT enhanced motility in cooled stallion sperm [9]. In epididymal stallion sperm, CF and PT enhanced motility and kinematic parameters [35,37], and also PT improved membrane integrity as tyrosine phosphorylation status remained unaffected [37]. Caffeine and PT seem to be more efficient in epididymal sperm than in ejaculated sperm because its ability to increase levels of cAMP appears to be more effective on quiescent sperm compared to already motile sperm [35].…”
Section: Discussionmentioning
confidence: 99%
“…Many reports demonstrate that using of specific substance such pentoxifylline improved the motion characteristics of fresh and post-thaw spermatozoa in different species, which exerts its effects probably by inhibiting cAMP-phosphodiesterase, thus TA B L E 1 Effects of pentoxifylline (PTX) and Basal Medium Eagle (BME) in diluents on motility and velocity characteristics of cryopreserved goat spermatozoa increasing the intracellular cAMP concentration (Bell et al, 1993;Duan & Goldberg, 2003;Gil et al, 2010;Guasti et al, 2013Guasti et al, , 2017Hassanpour et al, 2010;Maxwell et al, 1995;Milani et al, 2010;Mirshokraei et al, 2011;Thongtip et al, 2008). Moreover, PTX, as a phosphodiesterase inhibitor, has been postulated to cause an increase in tyrosine phosphorylation level being associated with an augmentation in spermatozoa motion and kinetic parameters, hyperactivity, acrosome reaction and conception's rate (Henkel & Schill, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Pentoxifylline (PTX), as a phosphodiesterase inhibitor in the methylxanthine group, is known to protect the spermatozoa during cryopreservation processes (Bell, Wang, Hellstrom, & Sikka, 1993; Duan & Goldberg, 2003; Gil et al., 2010; Guasti et al., 2013, 2017; Hassanpour, Mirshokraei, Tajik, & Haghparast, 2010; Maxwell et al., 1995; Milani et al., 2010; Mirshokraei, Hassanpour, Mehdizadeh, & Taheri, 2011; Thongtip et al., 2008). The suggestions above indicated that PTX stimulates the spermatozoa motion, acrosome reaction and fertilization rate by inhibition of cyclic adenosine monophosphate (Lardy, Garbers, Lust & First, 1971; Aitken, 1997; Armstrong, Clulow, Murdoch, & Jones, 1994; Yovich, 1993) which is additionally able to scavenge the ROS formation (McKinney, Lewis, & Thompson, 1996; Zhang, Sharma, Agarwal, & Falcone, 2005).…”
Section: Introductionmentioning
confidence: 99%